基于樟树籽油和棕榈油硬脂结构脂的开发及其在人造奶油中的应用Development of structured lipids based on camphor seed oil and palm stearin and its application in margarine - 高盼1,2， 张远鹏1， 王澍3， 周桐1， 殷娇娇1， 钟武1,2， 胡传荣1 GAO Pan 1,2, ZHANG Yuanpeng1, WANG Shu3, ZHOU Tong1, YIN Jiaojiao1, ZHONG Wu1,2, HU Chuanrong1 (Zhongguo youzhi)
旨在开发具有改善营养和功能特性的新型人造奶油产品，以樟树籽油（CSO）和棕榈油硬脂（PST）为基料油制备结构脂。在比较化学酯交换结构脂（CIE）和酶法酯交换结构脂（EIE）的甘油三酯及sn-2位脂肪酸组成、热力学性质（滑动熔点、固体脂肪含量）、流变学特性及晶型的基础上，选择一种结构脂用于制备人造奶油，分析了所制备的人造奶油的基本理化指标、硬度以及打发性。结果表明：酯交换明显改变了CSO和PST的甘油三酯和sn-2位脂肪酸的含量，CIE和EIE中均有中长碳链甘油三酯生成，主要是CCO、CCP、CLaO和LaPP，滑动熔点为31.8~41.5 ℃；CSO与PST质量比为5∶ 5和7∶ 3时所制备的EIE有良好的口融性；2种酯交换技术制备的结构脂均表现剪切变稀现象，均存在β′晶型和β晶型；选择CSO与PST质量比为3∶ 7的EIE为原料制备人造奶油，所制备的人造奶油酸值（KOH)（0.47 mg/g）、过氧化值（0.62 mmol/kg）、水分含量（13.79%）符合产品相关标准要求，且具有良好的打发性和硬度。综上，樟树籽油和棕榈油硬脂经酶法酯交换制备的结构脂，能够作为改善人造奶油营养特性的原料。 To develop a new type of margarine product with ehnanced nutritional and functional properties, camphor seed oil (CSO) and palm stearin (PST) were used as base oils, the structured lipids of CIE and EIE were prepared by chemical transesterification and enzymatic transesterification, respectively. By comparing the glyceride and sn-2 fatty acid composition, thermodynamic properties (sliding melting point, solid fat content), rheological characteristics, and crystal form of CIE and EIE, one type of structured lipid was selected to prepare margarine. The basic physicochemical indicators, hardness, and whipping property of the prepared margarine were analyzed. The results indicated that transesterification significantly altered the glyceride and sn-2 fatty acid contents of CSO and PST, with the generation of medium-long chain glycerides in CIE and EIE, mainly CCO, CCP, CLaO, and LaPP, and a sliding melting point ranging from 31.8 ℃ to 41.5 ℃. The EIE prepared with the mass ratio of CSO to PST 5∶ 5 and 7∶ 3 exhibited good mouth-melting properties. The structured lipids prepared by both transesterification technologies showed shear-thinning phenomena and both β′ and β crystal forms were present. EIE prepared with a mass ratio of CSO to PST 3∶ 7 was selected as the raw material for preparing margarine. The acid value (0.47 mgKOH/g), peroxide value (0.62 mmol/kg), and moisture content (13.79%) of the prepared margarine met the relevant standard requirements, and it had good whipping property and hardness. In conclusion, the structured lipids prepared by enzymatic transesterification of CSO and PST can be used as raw materials to improve the nutritional characteristics of margarine.